Lactobacillus Casei Decreases Organophosphorus Pesticide Diazinon Cytotoxicity in Human HUVEC Cell Line - Hasan Bagherpour Shamloo; Saber Golkari; Zeinab Faghfoori; AliAkbar Movassaghpour; Hajie Lotfi; Abolfazl Barzegari; Ahmad Yari Khosroushahi (Tabriz University of Medical Sciences, 2016)
Purpose: Exposure to diazinon can trigger acute and chronic toxicity and significantly induces DNA damage and proapoptotic effects in different human cells. Due to the significance of probiotic bacteria antitoxin effect, this study aimed to investigate the effect of Lactobacillus casei on diazinon (DZN) cytotoxicity in human umbilical vein endothelial cells (HUVEC) in vitro. Methods: The cytotoxicity assessments were performed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) test, DAPI (4',6-diamidino-2-phenylindole) staining and flow cytometric methodologies. Results: Cytotoxic assessments through flow cytometry/ DAPI staining demonstrated that apoptosis is the main cytotoxic mechanism of diazinon in HUVEC cells and L. casei could decrease the diazinon cytotoxic effects on toxicants. Conclusion: the screen of total bacterial secreted metabolites can be considered as a wealthy source to find the new active compounds to introduce as reducing agricultural remained pesticide cytotoxicity effects on the human food chain.